Armed conflicts and food insecurity - a short literature review - Dago, Eric (2021)
‘‘End hunger, achieve food security, improve nutrition and promote agriculture” is one of the stated goals of the 2030 agenda for sustainable development. A major obstacle to achieving this goal is the growing incidence of armed conflict, terrorism and state fragility in the developing world. This obstacle deserves to be understood in particular its relation with food insecurity. In this perspective, availability of data in conflict regions has allowed the economic literature to provide a better understanding of the relationship between conflict and food security. In this document, we analyze the relationship between armed conflict and food insecurity through a literature review.